An investigation into the inhibitory function of serotonin in diffuse noxious inhibitory controls in the neuropathic rat. (28th November 2016) - Bannister, K.; Lockwood, S.; Goncalves, L.; Patel, R.; Dickenson, A.H.
Abstract: Background: Following neuropathy α2‐adrenoceptor‐mediated diffuse noxious inhibitory controls (DNIC), whereby a noxious conditioning stimulus inhibits the activity of spinal wide dynamic range (WDR) neurons, are abolished, and spinal 5‐HT7 receptor densities are increased. Here, we manipulate spinal 5‐HT content in spinal nerve ligated (SNL) animals and investigate which 5‐HT receptor mediated actions predominate. Methods: Using in vivo electrophysiology we recorded WDR neuronal responses to von frey filaments applied to the hind paw before, and concurrent to, a noxious ear pinch (the conditioning stimulus) in isoflurane‐anaesthetised rats. The expression of DNIC was quantified as a reduction in WDR neuronal firing in the presence of conditioning stimulus and was investigated in SNL rats following spinal application of (1) selective serotonin reuptake inhibitors (SSRIs) citalopram or fluoxetine, or dual application of (2) SSRI plus 5‐HT7 receptor antagonist SB269970, or (3) SSRI plus α2 adrenoceptor antagonist atipamezole. Results: DNIC were revealed in SNL animals following spinal application of SSRI, but this effect was abolished upon joint application of SSRI plus SB269970 or atipamezole. Conclusions: We propose that in SNL animals the inhibitory actions (quantified as the presence of DNIC) of excess spinal 5‐HT (presumed present following application of SSRI) were mediated via 5‐HT7 receptors. The anti‐nociception depends upon an underlying tonic noradrenergic inhibitory tone via the α2‐adrenoceptor. Significance: Following neuropathy enhanced spinal serotonin availability switches the predominant spinal 5‐HT receptor‐mediated actions but also alters noradrenergic signalling. We highlight the therapeutic complexity of SSRIs and monoamine modulators for the treatment of neuropathic pain.